IMPROVING STUDENTS' MATHEMATICAL COMMUNICATION ABILITIES THROUGH THE PROBLEM BASED LEARNING LEARNING MODEL - Hafriani; Muhammad Yani; Dana Tasliana (LPPM Institut Ahmad Dahlan Probolinggo, 2025)
Mathematical Communication Skills (MCS) is not only a tool to convey mathematical ideas, but also an important part of the mathematics learning process. In fact, students' MCS is still very low and needs further action, so an alternative is needed that can develop better students' MCS. The purpose of this study was to determine the increase in students' MCS after the Problem Based Learning (PBL) learning model was applied. The research method used was a mixed method with concurrent triangulation design. Samples were taken using random sampling techniques from the total population of all students in class X MAN 1 Aceh Barat and students in class X MIA-6 were selected as research samples. Data were collected through tests and interviews which were then analyzed using normalized N-Gain and qualitatively. The results of the study found that the overall increase in students' MCS was in the medium and low categories, however, the increase in all indicators of students' MCS was quite good, where (1) students were able to communicate mathematical thinking coherently and clearly, (2) were able to use mathematical language to express mathematical ideas correctly, but some students made mistakes when making mathematical models, (3) were able to organize and consolidate mathematical thinking through communication, although some students were still confused about the steps to solve it, and (4) were able to analyze and evaluate mathematical thinking and strategies used by others. However, some students were only able to analyze and were less able to evaluate mathematical thinking and strategies used by others. Overall, students have had a good MCS.